The Impact of Teacher Qualifications and Experience on English Language Performance: A Case Study of Accredited Public and Private Secondary Schools in the City of Goma. - BELA ADASOPO Frank; MATSORO MITONDO Amédée; BASUAYI BULA Clément (IJRDO- Journal of Educational Research, 2024)
Our research focuses on The Impact of Teacher Qualification and Experience on English Performance. Case of approved public and private secondary schools in the city of Goma covering the period from June 1, 2023 to January 31, 2024. We used data collection and data analysis methods. On the other hand, data collection techniques, data collection tools and the Cronbach’s Alpha test to adjust the questionnaire. The sample size was generated by the Open Epi formula of which n=249 students. After a descriptive analysis, and interpretation of the variables using frequencies and percentages, we found that: In terms of performance, the results of the regression model show that the independent variables like class size and qualification affect the performance in the English language by 2.7%. The ANOVA test with F=9.285 and P value=0.000<0.05. This explains why the difference in the average scores obtained by students in the English tests in different schools is significant. The ANOVA test and the regression model show that our results are significant at the 0.05 level.